MicroRNA and cancer: a focus on mammary tumors in female dogs - Rosana Lino Salvador-Bernabé; Mirela Tinucci-Costa; Renee Laufer Amorim (Ciência Rural, 2018)
ABSTRACT: Mammary tumors are the most frequent tumors reported in female dogs and have great relevance in veterinary oncology; however, little is known about the molecular mechanisms involved in the development of metastasis. An increasing number of human studies have suggested that epigenetic alterations, such as DNA methylation, miRNA, and histone modifications, are the predominant events leading to the metastatic phenotype in tumor cells and participate in regulating oncogenic signals associated with tumor spread. Among these epigenetic alterations, miRNAs have stood out in recent years, presenting a fundamental role in tumorigenesis. There are still few studies evaluating the role of miRNAs in canine mammary tissues. Thus, this paper aims to review the role of miRNAs in cancer with a special focus on canine mammary tumors.